Unformulated illegality: Law students’ experiences in their contact with the professional world - Del Mastro Puccio, Fernando (2024)
In their first contact with the professional world, law students experience diverse situations in which the law that regulates their internships is violated. In this research, we seek to understand how law students formulate those experiences, that is, the way in which they give them a particular meaning. Drawing from hermeneutical approaches to psychoanalysis, we start by recognizing that the way in which people formulate their experiences is not neutral: between different possible meanings, people elude those that show an intolerable image of themselves and their context. In this paper, we argue that law students don’t formulate the situations they experience, in which regulation and their rights are violated, as illegalities and violations of professional ethics standards. On the contrary, in different manners, they justify what happens, adapting to the events with fatalistic views of the professions’ environment, which is presented as not regulated. This occurs in an institutional context (that of law schools) where these problematic situations are not recognized and are not pedagogically addressed, which makes it more difficult for law students to formulate them differently. By gaining consciousness on how they formulate their experiences and trying different formulations, law students’ might develop and increase their agency, in order to deal with situations in which regulation is infringed in the professional context.